2009
DOI: 10.1261/rna.1411809
|View full text |Cite
|
Sign up to set email alerts
|

Kinetoplastid guide RNA biogenesis is dependent on subunits of the mitochondrial RNA binding complex 1 and mitochondrial RNA polymerase

Abstract: The mitochondrial RNA binding complex 1 (MRB1) is a recently discovered complex of proteins associated with the TbRGG1 and TbRGG2 proteins in Trypanosoma brucei. Based on the phenotype caused by down-regulation of these two proteins, it was proposed to play an unspecified role in RNA editing. RNAi silencing of three newly characterized protein subunits, guide RNA associated proteins (GAPs) 1 and 2 as well as a predicted DExD/H-box RNA helicase, show they are essential for cell growth in the procyclic stage. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
195
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(203 citation statements)
references
References 47 publications
7
195
1
Order By: Relevance
“…Interestingly, the REL1 RNA ligase, a component of the RECC, and the S17 and L3 kinetoplast ribosome proteins also exhibited a concentration in the kDNA region of the mitochondrion, suggesting the intriguing possibility of a physical linkage of kDNA transcription, translation, and editing pathways, but this remains to be investigated. Our localization results differ somewhat from several previous studies that showed that editing proteins are distributed throughout the mitochondrion with no apparent concentration (36,37) and that the RNA-linked editing proteins, GAP1 and GAP2, are localized in discrete particles throughout the mitochondrion (14). These differences could be speciesdependent or could be due to technical details.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the REL1 RNA ligase, a component of the RECC, and the S17 and L3 kinetoplast ribosome proteins also exhibited a concentration in the kDNA region of the mitochondrion, suggesting the intriguing possibility of a physical linkage of kDNA transcription, translation, and editing pathways, but this remains to be investigated. Our localization results differ somewhat from several previous studies that showed that editing proteins are distributed throughout the mitochondrion with no apparent concentration (36,37) and that the RNA-linked editing proteins, GAP1 and GAP2, are localized in discrete particles throughout the mitochondrion (14). These differences could be speciesdependent or could be due to technical details.…”
Section: Discussioncontrasting
confidence: 99%
“…Repression of REH1 expression showed no effect on the stability or length of the gRNA 3′ oligo U tails (Fig. 1C), as was reported for the trypanosome REH2 mitochondrial RNA helicase (14,16) Real-time RT-PCR was also used to quantitate the effect of REH1 down-regulation on the relative abundance of several preedited and mature edited mRNAs ( Fig. 1D and Table S1).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations